EMOJI IN WRITING SYSTEMS - Vijaya, P.; Jose. S, Franklin Thambi (International Journal of Psychosocial Rehabilitation, 2020)
The 21st century has changed the world with its technology. Technology is science or knowledge which is placed into practical to solve or to invent new tools. Technology is closely associated with electronics. Due to this, all the electronic media started to use Emoji as a style in writing. Emoji is the smileys and ideographs used in electronic messages especially in internet related pages.A smiley is smart representation of a humanoid face with a smile where as an ideograph is a graphic symbol which signifies an idea or notion instead of a specific word or a phrase. Emoji came to exist in different genres such as human, human face expressions, objects that are commonly used, types of weather, animals, trees and plants. It replaced almost all the expressions involved in the mentioned different genres and becomes acceptable by the whole world. The word ‘emoji’ is an English adoption of Japanese word with meaning ‘picture’. Moreover, emoji stands for ‘letter’ or ‘character’. It became world famous after introducing it in the field of technology. This article aims to trace out the use of emoji in writing systems.,